Engineering education for sustainable development: using online learning to support the new paradigms - Sivapalan, Subarna; Clifford, Michael J.; Speight, Sarah (Taylor & Francis, 2017)
This paper explores the experiences of three academic members of the University of Nottingham Open Online Course (NOOC) and Massive Open Online Course (MOOC) team, comprising an engineer (tutor), an engineering education specialist (facilitator) and a specialist in higher education pedagogy (convenor). The paper explores notions of what makes for effective teaching of sustainability within a multidisciplinary online context, and the extent to which this experience has impacted upon personal behaviours and attitudes to sustainability, from an Engineering Education for Sustainable Development (EESD) perspective. Team members’ experiences are further supported by findings from student and learner evaluations of the NOOC and MOOC courses. Key findings of the research include (a) Interdisciplinarity is a strength of the course (b) The course can lead to genuine change in the understanding of sustainability; (c) Teaching sustainability online is different; (d) Involvement in the course impacts upon teaching practices; (e) Cultural and disciplinary diversity within both the course team and the student cohort is a major contributor to the overall sustainable development learning experience in the NOOC/MOOC. It is hoped that the findings of the study will pave the way for engineering and non-engineering educators to explore the potential of integrating sustainability within the modules they teach, via online teaching and learning means.